2009
DOI: 10.1080/10242690903105257
|View full text |Cite
|
Sign up to set email alerts
|

Military Expenditure and Unemployment Rates: Granger Causality Tests Using Global Panel Data

Abstract: This paper investigates the empirical relationships between military expenditure and unemployment rates. A set of global panel data on 46 countries is utilized, and a panel data version of the Granger causality test is applied. The results indicate that there is little evidence of the causality running from unemployment to military expenditure regardless of how we measure military spending and determine group countries. In contrast, the causality running from military expenditure to unemployment receives empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Dunne and Smith (1990) report that the sample dynamic reduced form regressions estimates do not indicate that military spending share has a significant effect on the unemployment rate for the US and the UK, and pooled post-war data for 11 OECD countries. Tang et al (2009) observe that the causality running from military spending to unemployment is not statistically significant if military spending is measured by per capita military expenditure, however, it is significant predominantly for low-income and non-OECD countries, if it is measured by the military burden for 23 OECD and 23 non-OECD countries during 1988-2004. Mpanju (2012 reveals that there is a close positive linkage between FDI and employment in Tanzania during 1990-2008.…”
Section: Introductionmentioning
confidence: 91%
“…Dunne and Smith (1990) report that the sample dynamic reduced form regressions estimates do not indicate that military spending share has a significant effect on the unemployment rate for the US and the UK, and pooled post-war data for 11 OECD countries. Tang et al (2009) observe that the causality running from military spending to unemployment is not statistically significant if military spending is measured by per capita military expenditure, however, it is significant predominantly for low-income and non-OECD countries, if it is measured by the military burden for 23 OECD and 23 non-OECD countries during 1988-2004. Mpanju (2012 reveals that there is a close positive linkage between FDI and employment in Tanzania during 1990-2008.…”
Section: Introductionmentioning
confidence: 91%
“…Prior studies such as Paul (1996) and Tang, Lai, and Lin (2009) found that different countries show different causality directions between military spending and unemployment. This suggests that the military spending-unemployment relationship may be country specific, and thus, it is necessary to recognize the heterogeneous nature of the countries under investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Using Taiwanese data, Huang and Kao (2005) find that defense spending negatively affects employment growth in the short run, but positively in the long run. Wing (1991) finds that defense spending gives rise to considerable employment in Indonesia between 1978and 1980. Tang, Lai, and Lin (2009 investigates the relationships between military expenditure and unemployment rates for a global panel data on 46 countries and they found that there was a little evidence of the causality running from unemployment to military expenditure regardless of how they measured military spending and country classifications.…”
mentioning
confidence: 97%
“…The lag order is chosen by the Schwarz Bayesian Information Criterion, which chooses one lag for all countries except the US, where two lags are chosen. Above the countries were treated individually, but much of the recent work on military expenditures and GC has treated the multiple countries as a panel (e. g. Tang et al, 2009). Testing for GC in panels raise a range of further econometric issues.…”
Section: Other Countriesmentioning
confidence: 99%
“…For instance, Dunne and Smith (1990), in the first issue of this journal, could not reject the hypothesis of GNC in both directions between the share of military expenditure and unemployment in a sample of OECD countries. Tang et al (2009) also test for GNC using global panel data and find no evidence for GC from unemployment to military expenditure, but some evidence for GC from military expenditure to unemployment for non-OECD countries. There are also many studies testing GNC between military expenditure and other economic variables, particularly output; early examples being Joerding (1986), Kinsella (1990), Chowdhury (1991), Chen (1993) with more recent examples being Abu-Bader and Abu-Qarn (2003) and Kollias et al (2004Kollias et al ( , 2007, who also take account of the possibility of cointegration.…”
Section: Introductionmentioning
confidence: 99%